Kitchen gas stove table top height from ergonomic perspective for elderly in Malaysia / Ruhaizin Sulaiman - Sulaiman, Ruhaizin (2015)
Malaysia is expected to become an aged society by year 2020, hence there is a need to prolong the independency of its senior citizens by improving their residential environment. This thesis aimed to increase elderly independency and their quality of life by ergonomic means to let them live independently as long as possible. The main research question is; what is the role of ergonomics in enhancing comfort perception for improving residential built environment for the Malaysian elderly population? Besides this main research question, there are four sub-research questions in this study namely; what is the present state of living among elderly population in Malaysia, which ergonomic factors are affecting task performance of elderly population in their homes, what are the significant factors for enhancing comfort perception among elderly person when they perform their tasks, and what are the recommendations for ergonomic interventions that could enhance comfort perception for improving residential built environment for the elderly population. From these research questions some construct descriptions were identified. They are elderly population, ergonomics, enhanced comfort perception, and improved residential built environment. From these constructs four research objectives were structured. They are; to understand the present state of living among elderly population in Malaysia, to identify significant ergonomic factors that affecting task performance of elderly population in their homes, to determine significant anthropometric dimensions that could enhanced comfort perception among elderly person when performing their task in the kitchen, and to develop anthropometric workstation design model that could enhance comfort perception for elderly in the kitchen. The main hypothesis was ‘Comfort Perception improved (when) Postural Measurement and Physiological Limitation matched with acceptable range during task performance’. Chapter 1 is the introduction of the thesis. It consists of background study, issues relating to elderly in Malaysia, problem statements, research questions, research objectives, theoretical framework, inquiry strategy, expected findings, scope and limitation, significance of study, expected contribution and explains the organization of the thesis. Chapter 2 presents the literature review on ergonomics, enhance elderly comfort perception, task performance and improving residential built environment. Chapter 3 presents the method used, the subjects, apparatus and type of data. The eagle table research framework provides explicit information regarding the whole methodology of this study. This includes general survey, elderly critical task, major data acquisition, and validating elderly comfort perception. Chapter 4 explains the result of the study includes selection of subjects, elderly demography, results from the survey. It also presents the result of affecting factors against activity of frying such as postural assessment, physiology, anthropometry, kitchen environment and kitchen triangle distance. Chapter 5 explains the prototype fabrication and testing, setting-up the experiment, results of postural assessment and Rapid Entire Body Assessment (REBA), formulation to predict custom stove height and discussion on experiment. Chapter 6 explains ergonomic design criteria, proposed ergonomics design model, discussed on guidelines and challenges in elderly research. Chapter 7 summarizes the output and knowledge contribution of the study. This includes the key findings, limitation of the research and major contribution. Finally suggests what could be done for future work. There are 30 subjects taking part in this study. They are aged between 60 to 83 years with the mean of age at 67.1 year. From the survey, frying was identified as most important and most tiring task. It was then selected to be the case study. Three environmental parameters obtained from the study were temperature (26.0°C), light (800 lux) and relative humidity (70.0%RH). Based on the findings ten kitchen triangle distances were exceeded 792cm (26’) of the National Kitchen and Bath Association (NKBA) guidelines. Volume of Oxygen (VO2) was used to measure physiological limitation. Based on the results, severity of five minutes frying task for Malaysian elderly could be classified as “Light Work”. However, eight elderly were found having higher volume of oxygen consumption. The anthropometry measurements were applied to estimate frying task envelope. The elbow height and elbow-thumb-tip length were used with the equation to predict individual stove height. Postural measurements were applied to evaluate armpit angle and elbow angle whilst performing frying task. It proved that many elderly having the wrong stove height that could cause fatigue. REBA score was done twice; observation on actual frying task in elderly’s kitchen (90% at medium risk) and observation on frying task using the adjustable table-top with their preferable height (0.07% at low risk and 99.93% safe). It proved by improving the elderly comfort perception could improve the frying task and increased their quality of life. Cornell body parts diagram was used with questionnaire to evaluate strain, pain and fatigue among the elderly upon frying. It was found upper arm, shoulder, neck and upper back, and lower back rated at ‘very fatigue’. Results from this study shows that the most significant comfort perception factor was the stove height. It has relationships with anthropometry, task performance, strain and fatigue, physiological limitation and postural measurement. An adjustable table-top was designed and fabricated to test and validate the equations for setting individual stove height based on his/her anthropometry. It was found that the elderly preferable stove height were within the range of what was calculated by the equation. Therefore the equation could be used to predict individual stove height. In conclusion, the increase in the aging population in Malaysia is inevitable. The aged population has its own unique problems and will generate new challenges and demands to designers, engineers and ergonomists. We will all age and we later on become independent and require the services for the aged at some point in time.